Artificial Intelligence: An Algorithmic Mechanism of Institutionalizing the Social Imaginaries of a Dehumanized Global Society? - Quispe-Mamani, Edgar; Salas-Ávila, Dante Atilio; Torres-Gonzales, Tania Paola; Alvarez-Siguayro, Raquel; Torres-Cruz, Fred; Collanqui, Pascual Ayamamani; Belizario-Quispe, German (Journal of Posthumanism, 2025)
In the context of the information and network society, with the incorporation of information and communication technologies, one of the most marked and controversial challenges of this last decade has been the growing integration of artificial intelligence (AI) systems in contemporary society, generating a series of ethical, social, economic and political dilemmas that deserve to be addressed. Therefore, the objective of the study is to analyze the implications of AI systems in the workplace and in daily social interactions. Applying the methodological approach of qualitative research, based on the methodological design of interpretive phenomenology, semi-structured and in-depth interviews have been conducted with 20 researchers and intellectuals from 11 countries of the Ibero-American continent: Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Spain, Mexico, Peru, Uruguay and Venezuela; all the participants in the study are associate members of the Ibero-American Network of Imaginaries and Representations. The findings reveal that, based on the established core social imaginary of “AI as an expression of modern Western instrumental rationality”, social imaginaries have been institutionalized, both regarding the implications of AI in the workplace and in everyday social interactions. In the first case, the social imaginaries of ethics in AI systems, the reproduction of socioeconomic inequalities and the complementarity between human beings and AI stand out; while, in the second case, the institutionalization of social imaginaries of dehumanization of AI, social alienation of humans from their being and algorithmic subjugation of everyday social life stand out. In short, given the configuration of the dominant social imaginary of the “new global order based on AI systems”, the research calls for the construction and institutionalization of the radical social imaginary of practical ethics in AI systems, which translates into technological policies and regulatory frameworks at a global and local level, implementing socio-institutional transformations, based on the paradigm of multilevel and multidimensional governance.